Commentaries on "Evaluating the Geographic in GIS". Issue 3 (1st July 2019) - Warren, Stacy; Harris, Trevor; Goodchild, Michael; Solís, Patricia
Abstract: In this article, four geographers who are also practitioners critique "Evaluating the Geographic in ." Sparked by the arguments in that article, they pose fundamental questions about how geography can best contribute to practices.